A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP N 18 PEKANBARU IN COMPREHENDING PROCEDURE TEXTS - Purba, Ervina Nova; Gultom, Effendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The objective of this study is to find out the ability of thesecond year students of SMP N 18 Pekanbaru in comprehendingprocedure texts. Based on the result of the data analysis in chapter IV,the writer makes some conclusions. Among 40 students, no studentis in excellent level and very poor level, 13 students (32.5%) are ingood level, 25 students (62.5%) are in mediocre level, 2 students (5%)are in poor level. The mean score of the whole students incomprehending procedure texts is 57.81. In conclusion, the ability ofthe second year students of SMP N 18 Pekanbaru in comprehendingprocedure texts is at mediocre level. Since the research dealt withcomprehending procedure texts, the writer drew conclusions for eachclassification of comprehending procedure texts. In terms of findingmain idea, from 40 students, 5 students (12.5%) are in excellent level,24 students (60%) are in good level, 3 students (7.5%) are inmediocre level, 7 students (17.5%) are in poor level and 1 student(2.5%) is in very poor level. In terms of finding factual information, 4students (10%) are in excellent level, 24 students (60.%) are in goodlevel, 8 students (20%) are in mediocre level, 3 students (7.5%) are inpoor level and 1 student (2,5%) is in very poor level. In terms offinding meaning of difficult word, 6 students (15%) are in excellentlevel, 21 students (52,5%) are in good level, 10 students (25%) are inmediocre level, 2 students (5%) are in poor level and 1 students(2.5%) is in verypoor level. In terms of identifying reference, nostudent (0%) is in excellent level, 11 students (27.5%) are in goodlevel, 13 students (32.5%) are in mediocre level, 14 students (35%) arein poor level and 2 students (5%) are in very poor level. In terms ofmaking restatement, from 2 students (5%) are inexcellentlevel, 10students (25%) are in good level, 12 students (30%) are in mediocrelevel, 16 students (40%) are in poor level and no student (0%) is invery poor level.